Keterlibatan Perempuan Dalam Sektor Pertanian Untuk Menunjang Kesejahteraan Keluarga Menurut Perspektif Feminisme (Studi Kasus Di Desa Songan, Bangli, Bali) - Ni Luh Sinta Yani; Luh Indrayani (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This research aims todescribe the factors that cause Songan’s women to be involved in the agricultural sector, describe the involvement of women in the agricultural sector to support family welfare, and describe the feminist view of women farmers in Songan Village. This research used a qualitative approach with a case study method. The information collected using data triangulation, namely participatory observation, in-depth interviews, and documentation studies. The validity of the data was tested using triangulation of sources. The results and discussion showed that there are four factors that cause Songan’s women to be involved in the agricultural sector, namely geographic factors, economic pressure factors, habit factors, and educational factors. Songan’s women have two very important roles in improving family welfare, namely playing a role in agriculture and in the household. Feminist values have been applied indirectly in Songan village because women have the same opportunities as men.